Study the effect of zinc oxide nanoparticles on degradation, antibacterial, thermal and morphological properties of polyvinyl alcohol films - Sabr Ohood Hmaizah; Obaid Massar Najim; Al-Mutairi Nabeel Hasan; Krynke Marek; Mielczarek Krzysztof (Production Engineering Archives)
In this study, a film was prepared from polyvinyl alcohol (PVA) and zinc oxide (ZnO) nanoparticles (nano-ZnO) via the casting method. Nanoparticles were added to PVA biopolymer to create reinforced biocomposite films with different loading contents (2, 4, and 6 wt.%), and they were tested by performing the following assays: the FTIR test, the antibacterial, soil burial test, DSC, AFM, and SEM. The results showed an improvement of the membranes in the antibacterial properties for both Escherichia coli (E. coli, Gram-negative) and Staphylococcus aureus (S. aureus, Gram-positive) when nano-ZnO was added. The biodegradation through weight loss was observed for all samples, and the results showed that the weight loss increased with the increase in ZnO nanoparticle content from 2% to 6% wt. The DSC results showed that the addition of ZnO led to an increase in Tg, and increasing the degree of glass transition led to an increase in the degradation rate. In the FTIR results, only physical interference was observed; no chemical interference was evident. The AFM results showed some agglomerations of nano-ZnO in the PVA matrix led to an increase in the surface roughness of the PVA/nano-ZnO film.